Split-ring resonator-based antenna with photonic band gap for UHF RFID tag - Erman, Fuad Naim Ahmed (2016)
RFID system is to transfer data on a transponder (tag) that can be retrieved with a transceiver by means of wireless connection. The whole operation is weather independent and non-line-of-sight. These features for ID system overcome the limitations of optical barcodes. RFID tags are comprised of integrated circuit (IC) and an antenna. The IC executes all of the data processing and is powered by extracting power from the interrogation signal transmitted by the RFID reader. The tag antenna determines the amount of power transmitted from the reader to the tag and the reflect signal from the tag to the reader. Nevertheless, there are no constraints on the physical parameters of the reader’s antenna, such as being planar or small in size, these constraints do stratify on the tags antenna. In fact, the tag miniaturizing is limited by the tag antenna size. This thesis reports on the design, fabrication, and measurement of Ultra High Frequency (UHF) RFID tag antennas for 860 to 960 MHz which can be used in metallic applications. The presented tag antennas are designed and fabricated to accomplish low tagging costs, good performance, for tagging metallic objects. Split-ring resonator-based tag antenna with regular ground plane was designed and tested. In this design, a compact antenna is proposed and designed for metallic objects UHF RFID (860-960) MHz. The antenna structure etched on polytetrafluorethylene (PTFE) substrate. The slim antenna has been proposed with proximity coupled feeding, two split ring structure mounted to each side of the tag chip and it is fed by two symmetrical C-shaped resonators with outer strip lines. The antenna size is 83.7×62.8×1.57 mm3 at operating frequency. The peak gain and read range of the antenna reached to -1.445 dBi and 0.5 m respectively when it is placed on 400×400 mm2 metallic surface. The antenna bandwidth is 20 MHz (power reflection coefficient lower than -3 dB). This antenna introduced to fill up the need for tagging for long range and mounted for metallic objects such as oil barrels tagging in petrol refineries and gas cylinders Photonic band gap (PBG) structure integrated to enhance the gain. The PBG structure formed by etching a periodic pattern of circles in the ground plane. The total gain and read range of this design are -0.72 dBi and 0.53 m respectively when it is mounted on 400×400 mm2 metallic plate. The percent of gain improvement is around 49.76% when PBG integrated in the design. The antenna bandwidth at half power bandwidth is 17.8 MHz. The impedance of the suggested antennas was simulated then measured to validate the design. The presented RFID tag antennas are low cost, compact, and with good gain that make it fit for tagging metallic applications.